The Influence of Halal Awareness and the Image of Halal Destinations on Visit Intentions in Halal Culinary Tourism in Banten Province - Fajar Hidayatullah; Sulaeman Jazuli; Wazin; Suryani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Halal culinary tourism has become an increasingly important segment of the global tourism industry as Muslim tourists seek destinations that align with religious values while offering authentic culinary experiences. This study examines the relationship between halal awareness, halal destination image, and visit intention for halal culinary tourism in Banten Province. This study uses a quantitative approach, data was collected from 147 respondents through targeted sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that halal awareness has a significant positive influence on the image of halal destinations and the intention of visiting in Banten Province. The image of halal destinations also has a strong and positive influence on visit intentions, which confirms its central role in shaping tourist behavior decisions in Banten Province. The findings suggest that halal awareness serves as a fundamental cognitive mechanism that reinforces the perception of the destination and reduces perceived uncertainty, while the image of the halal destination consolidates this perception into a strong foundation for travel intentions. This study contributes to the halal tourism literature by empirically validating the integrated role of destination awareness and imagery in halal culinary tourism and offers practical insights for destination managers seeking to increase competitiveness through halal-oriented strategies.